Teachers' perspectives of social and emotional learning in Aotearoa New Zealand primary schools. Issue 1 (11th June 2019) - Dyson, Ben; Howley, Donal; Shen, Yanhua
Abstract : Purpose: The purpose of this paper is to study teachers' perspectives of social and emotional learning (SEL) in Aotearoa New Zealand (NZ) primary schools. Design/methodology/approach: This research was a case study design investigating the phenomenon of SEL in primary schools (elementary school level) in Aotearoa NZ (Stake, 2005). Findings: The SEL themes that were drawn from the data were: positive interdependence, empowerment, self-management, self-awareness restorative conversations and circle time. Research limitations/implications: The research challenges the field to work with teachers and community workers to create more in-depth qualitative research knowledge that is contextually relevant to SEL for researchers, educational policymakers and our children. Originality/value: Based in Aotearoa NZ primary schools, this qualitative research provides a unique perspective of SEL from school-based practicing teachers.